Direct patient costs for drugs and consumables at fifteen health facilities in Southern Madagascar, a secondary analysis of patient invoices - Franke, Mara Anna; Neumann, Anne; Nordmann, Kim; Suleymanova, Daniela; Ravololohanitra, Onja Gabrielle; Knauss, Samuel; Emmrich, Julius (PLOS ONE, 2024)
BACKGROUND: Financial risk protection in health is a key objective of the Sustainable Development Goals. However, financial risk protection mechanisms are limited, especially in low-income countries, such as Madagascar. To design effective financial risk protection mechanisms, solid and reliable data on the costs patients incur when seeking care are essential. With this study, we therefore aim to describe medical costs for drugs and consumables for patients as well as model the likelihood of catastrophic health expenditure at fifteen health facilities in Southern Madagascar. - METHODS: We conducted a costing analysis of patient invoices from fifteen health facilities (four primary and eleven secondary facilities) in Southern Madagascar, including public, private, and faith-based facilities. We included invoices from patients accessing care for life-threatening conditions, accidents and injuries, paediatric, or maternity care between February 2021 and July 2022. Costing data were limited to costs for drugs and consumables. We used regional household expenditure data from a representative household survey to calculate the incidence of catastrophic health expenditure in our sample. - RESULTS: We analysed data from 9,855 cases, including 4,980 outpatient cases, 3,447 inpatient cases without surgical intervention, and 1,419 surgical cases. The average patient cost for drugs and medical consumables across all cases was USD 39.52 (range: USD 0.13-1,381.18, IQR: USD 9.07-46.91). Average costs for surgical treatment were USD 119.33 (range: USD 8.10-522.88, IQR: USD 73.81-160.49), for inpatient treatment USD 47.07 (range: USD 1.82-1,381.19, IQR: USD 22.38-58.91), and for outpatient treatment USD 11.73 (range: USD 0.15-207.79, IQR USD: 6.00-15.53). On average patients at faith-based facilities paid USD 47.20 (range: USD 0.49-530.33, IQR: 10.74-58.54), USD19.47 (range: USD 0.40-1,381.23, IQR: 6.77-24.07) at private facilities, and USD 34.65 (range: USD 0.58-245.24, IQR: USD 6.08-60.11) at public facilities. Patients requiring surgical care were most likely to experience catastrophic health expenditure and average costs for maternity care were significantly higher than for other patient groups. - CONCLUSIONS: Financial risk protection schemes in Madagascar, such as the national UHC policy, and the national solidarity fund, as well as interventions by non-governmental and multilateral organisations, need to focus on surgical cases and maternity care to protect vulnerable populations from catastrophic health expenditures for life-threatening conditions, accidents and injuries, and maternity and paediatric care.
Gesehen am 13.06.2025